REDESAIN VISUAL PERMAINAN KARTU ‘THE ART OF BATIK’ - Jennifer Audiah; Brian Alvin Hananto (Prahasta Publisher (manage by: DRPM Institut Bisnis dan Teknologi Indonesia), 2019)
Previously, the author had done a study towards ‘The Art of Batik’ board game in terms of graphic design, especially in the aspect of information grouping and visual hierarchy. From that study, it is found that some game component there was too much information that wasn’t properly visualized and there was lack of visual hierarchy. This drives the author to conduct a redesign in response to the findings that were previously found. This paper will discuss the redesign of the 'The Art of Batik' card game that was made by the authors. The paper will describe the steps and design considerations that were made in the design process. At the end of the design, the authors conclude the paper and give a recommendation on how to design a game from the perspective of a visual communication designer. The authors hope that this paper can be a reference for further game design and game visual designs. The design process was based on the paradigm that each design needs to accommodate a hierarchy of needs before attempting to pursue additional features. With that principle in mind, the authors remapped the pieces of information of the game and redesigned the form of the game components. The result was a playable new set of 'The Art of Batik' that is ready to be evaluated in further research.